Relationships between teaching competence, motivational factors, and knowledge sharing behavior at a professional learning institution in Malaysia - Sulaiman, Sarinah (2012)
In spite of the many types and forms of organizational supports invested to encourage knowledge exchange in organizations, the level of knowledge sharing among employees is still at a moderate level or below optimal. This is because knowledge sharing is still seen as largely an individual person’s effort and is often unnatural. Thus the question arises as to what the most influential factors are in determining the teachers’ knowledge sharing behavior (KSB), particularly in the educational context. Hence, this study aimed to examine the teachers’ KSB at aprofessional learning institution and how it is related to their teaching competence,personal motivational factors and organizational support. In addition, the demographic variables that include age, gender, highest education attainment teaching qualification, and the number of years in teaching were also used to examine their influence on the KSB of the teachers. With a total population of 310 teachers conducting diploma programs for the students, this study employed a quantitative survey using self-administered questionnaire initially distributed to all teachers in this institution. The questionnaire that was written in English, received acceptable responses from 150 teacher respondents with a response rate of 48%. The statistical tests conducted were mean and standard deviation, independentsamples t-test, one-way ANOVA, bi-variate correlation, and standard multiple linear regression. Face validity was assured by distributing the measurement scales to two experts in the Faculty of Educational Studies of Universiti Putra Malaysia. All the Cronbach’s alpha coefficients of the scale in the pilot test and actual study were above the acceptable value, ranging from .841 to .974, which was above the threshold value of .70. Teaching competence was found to be strongly related to KSB (r =.517 and p<.01), while personal motivational factors (r = .471, p = .0001) and organizational support had moderate relationships (r = .328, p =.0001) to knowledge sharing. An independent-samples t-test showed no difference in the mean scores for the KSB between genders. Similarly, there was no difference in the mean scores for the KSB between teachers with bachelor’s degree and teachers with master’s degree as their highest qualification. A one-way ANOVA did not reveal a significant difference in the mean scores of the KSB among teachers of different age groups, or among teachers with different years of teaching experience in this institution. Teaching competence, personal motivational factors and organizational support were found to significantly explain the variance in KSB. With regard to the sub-factors of the personal motivational factors, only personal interaction behavior was found to be significant in explaining KSB. Organizational commitment and perceived benefits were found to be insignificant in predicting KSB of the teachers. Among teaching competence sub-factors, competence in planning and preparation, and competence in delivering instruction were significant in explaining the variance of KSB. In addition, two sub-factors of organizational support significantly explained the variance in KSB: the provision of technical support services and the provision of technology support. With specific factors that significantly explain KSB, this study provides meaningful guidance to the institution’s management in order to facilitate the KSB of the teachers.